A late Wittgensteinian approach to early Christian apophaticism - Sadıkoğlu, Çetin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis investigates the possibility of a ground on which language can provide us with an opportunity to talk about God, despite the concerns about His ineffability as argued by religious apophaticism. Apophaticism is basically the idea that reality cannot be grasped by language. I begin by an exploration of what apophaticism is, and offer a specific form of apophatic thinking, namely, religious apophaticism. After I analyze how Plotinus argues for ineffability, I will move onto the early Christian reception of his apophatic thinking, via negativa, as it appears in the works of Gregory of Nyssa and Pseudo Dionysius. The form of religious apophaticism I will outline here holds the idea that God is so transcendent that He cannot be represented in language or in any other medium. I will then present an analysis of religious apophaticism from the perspective of philosophy of language. A religious apophaticist believes that a concept cannot be applied to God and a natural being at the same time because s/he believes that there is an incommensurability between the beings to be represented. I will argue against this idea by bringing examples from Wittgenstein’s arguments for language games and critique of ostensive definition. In the last chapter, I will show why it is problematic to hold a radical approach as regards the continuity in the application of concepts. I will look into the contrast between literalism and apophaticism, and argue that both positions are problematic. Finally, I will offer an analogical position to resolve the issue, and propose that to talk about God meaningfully, one needs to take into account the context in which the concept of God is constituted because language does not only describe facts.
Keywords: Religion -- Philosophy.; Negative theology.